2019
DOI: 10.1177/2010105818820006
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability and dengue in Singapore, Fiji, and Hong Kong: small bite, big threat

Abstract: Creative Commons Non Commercial CC BY-NC: This article is distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 License (http://www.creativecommons.org/licenses/by-nc/4.0/) which permits non-commercial use, reproduction and distribution of the work without further permission provided the original work is attributed as specified on the SAGE and Open Access pages (https://us.sagepub.com/en-us/nam/open-access-at-sage).Dengue is highly sensitive to climatic conditions, especially temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In Singapore, S-REITs operate under a supportive and transparent framework established by the monetary authority of Singapore, featuring clear reporting requirements and tax transparency. This contrasts with the M-REITs, which contend with a less investor-friendly regulatory landscape marked by higher withholding taxes and less transparency (Ong, 2019). These regulations facilitate the growth and global diversification of S-REITs, aligning with the study's findings that diversification in a mature market like Singapore may not add significant value due to the sophisticated nature of investors and their ability to diversify independently.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…In Singapore, S-REITs operate under a supportive and transparent framework established by the monetary authority of Singapore, featuring clear reporting requirements and tax transparency. This contrasts with the M-REITs, which contend with a less investor-friendly regulatory landscape marked by higher withholding taxes and less transparency (Ong, 2019). These regulations facilitate the growth and global diversification of S-REITs, aligning with the study's findings that diversification in a mature market like Singapore may not add significant value due to the sophisticated nature of investors and their ability to diversify independently.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Dengue fever is characterized by non-specific flu-like symptoms such as chills, appetite loss, lethargy, and low backache. According to a recent WHO research, dengue fever grew in several countries in 2020, including Bangladesh, Brazil ( 16 ), the Cook Islands, Ecuador, India ( 17 ), Indonesia ( 18 ), the Maldives, Mauritania, Mayotte, Nepal, Singapore ( 19 ), Sri Lanka, Sudan, Thailand ( 20 ), Timor-Leste, and Yemen. In 2019, dengue fever cases reached an all-time high in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Climate and weather are substantial variables in determining Aedes mosquito’s ecology, development, survival, and behavior as the primary vector of dengue ( Alkhaldy, 2017 ). Seasonal variations of environmental climate are also associated with the existence and the expansion of mosquito breeding sites, which support the abundance of vector population on a certain period ( Arcari et al., 2007 ; Ong & Tan, 2019 ; Williams et al., 2015 ). Temperature, humidity, and rainfall can directly influence the growth at all phases of mosquito’s life cycle that may indirectly affect the dengue transmission cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The entomological parameters regarding mosquito development and virus transmission are climatically sensitive for many reasons ( Putra & Nuraini, 2017 ; Russel et al., 2009 ). For example, numerous previous researches have identified that variation on temperature affects mosquito vectorial capacity, i.e., frequency of biting activity, vector mortality rate, and virus transmission effectiveness ( Li et al., 2017 ; Liu-Helmersson et al., 2014 ; Ong & Tan, 2019 ). Higher temperature shortens the vector development period, increases the intensity of blood-feeding, and decreases the extrinsic incubation period’s duration among female mosquitoes ( Ebi & Nealon, 2016 ; Sharmin et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%